The Role of Islamic Social Finance in Covid-19 - Trisno Wardy Putra; Trimulato Trimulato; Muhlis Muhlis; Farid Fajrin; Supriadi Supriadi (Universitas Islam Negeri Alauddin Makassar, 2020)
The focus of this research is to discuss the role of Islamic social finance especially zakat, infaq, alms and endowments in the face of the covid-19 pandemic. This study uses qualitative and descriptive methods with techniques for studying literature (library research). The results showed that Islamic social finance can be a solution in handling Covid-19, by using zakat funds, donations and alms in meeting consumptive needs and endowment funds used in health infrastructure assistance.